2016
DOI: 10.1177/0961203316651747
|View full text |Cite
|
Sign up to set email alerts
|

Hughes syndrome and epilepsy: when to test for antiphospholipid antibodies?

Abstract: Epilepsy and seizures are reported among the neurological manifestations of antiphospholipid syndrome (APS) at a prevalence rate of approximately 8%, which is nearly 10 times the prevalence of epilepsy in the general population. The association of seizures with antiphospholipid antibodies (aPL) is even more significant in the presence of systemic lupus erythematosus (SLE). In this review, we discuss the epidemiological, pathophysiological, laboratory, clinical, and radiological aspects of this association, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 105 publications
(209 reference statements)
0
11
0
Order By: Relevance
“…The exact pathogenesis of seizures related to APS is unknown, in part due to the combined inclusion of primary and secondary APS in most cohorts. Nevertheless, there are several proposed mechanisms including microthrombosis-induced ischemia leading to vascular epilepsy, aPL neuronal binding and injury, aPL-mediated inhibition of GABA receptors, and immune-mediated neuronal damage [ 69 , 71 , 72 ]. Although there have been several studies assessing the association of aPL with seizures or epilepsy in primary and secondary APS patients, results have been contradictory (see Noureldine et al [ 72 •] for a review).…”
Section: Neurological Manifestations Of Apsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact pathogenesis of seizures related to APS is unknown, in part due to the combined inclusion of primary and secondary APS in most cohorts. Nevertheless, there are several proposed mechanisms including microthrombosis-induced ischemia leading to vascular epilepsy, aPL neuronal binding and injury, aPL-mediated inhibition of GABA receptors, and immune-mediated neuronal damage [ 69 , 71 , 72 ]. Although there have been several studies assessing the association of aPL with seizures or epilepsy in primary and secondary APS patients, results have been contradictory (see Noureldine et al [ 72 •] for a review).…”
Section: Neurological Manifestations Of Apsmentioning
confidence: 99%
“…Nevertheless, there are several proposed mechanisms including microthrombosis-induced ischemia leading to vascular epilepsy, aPL neuronal binding and injury, aPL-mediated inhibition of GABA receptors, and immune-mediated neuronal damage [ 69 , 71 , 72 ]. Although there have been several studies assessing the association of aPL with seizures or epilepsy in primary and secondary APS patients, results have been contradictory (see Noureldine et al [ 72 •] for a review). Clinical manifestations are protean, and all types of seizures may be reported, including electroencephalographic abnormalities without clinically evident seizures [ 46 , 72 ].…”
Section: Neurological Manifestations Of Apsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the prevalence rate of epilepsy and seizures as neurological manifestations of APS is nearly 10 times higher than that in the general population [16]. Evidence suggests that 20% of idiopathic juvenile epilepsy cases are associated with aPL.…”
Section: Discussionmentioning
confidence: 97%
“…APS seems to confer a higher risk of developing seizures, with an estimated prevalence of ~8% ( 67 ), which may further increase in APS secondary to SLE ( 68 ). All forms of epilepsy may be seen, including subclinical forms, determined by the presence of abnormal electroencephalography findings alone ( 46 ).…”
Section: Neurological Manifestations Of Apsmentioning
confidence: 99%